Sostenibilità e partecipazione in due aree rurali marginali: una comparazione di progetti di sviluppo locale - Oscar Biffi (EtnoAntropologia)
The aim of this research is to study attempts of transition to sustainability in marginal rural area of the Italian mountains, comparing two cases characterized by distinct historical, geographical and cultural contexts. The San Martino and Stura valleys are compared and contrasted regarding their investments on local sustainable agriculture and ecomuseums. In both cases, local associations and institutions value heritage and landscape conservation. However, collaboration and communication between local networks and administrations is notable in one case and absent in another. Secondly, both the experiences - which to a point represent a bottom-up and a top-down sustainability initiative – suffer from a lack of democratic decision-making in their internal governance.